Efektivitas Analisis Butir Menggunakan Anajohn, Anates Dan Iteman Studi Soal Usbn Pelajaran Sejarah Kota Padang - Rizqa Hamalliya Putri; Ofianto Ofianto (Jurnal Kronologi, 2019)
This research aims to determine the quantitative analysis of the National Standard School Examination (USBN) questions on the history of Padang City High School in 2018/2019 school year using the Anajohn, Anates and Iteman programs. And to know the comparison of the effectiveness of programs in analyzing the quality of items and beneficial for the value of students. This research is quantitative descriptive. The subjects this research were students of class XII of SMA Negeri 2 Padang, SMA Negeri 4 Padang, and SMA Negeri 12 Padang. The data obtained were analyzed using three programs, namely Anajohn, Anates and Iteman. The results of the study showed: (1) Validity, in the Anajohn package A program there were 20 questions or 50% were declared valid and 18 questions or 45% were declared invalid, while there were 2 questions or 5% were not validated. In package B there are 30 questions or 75% declared valid and 10 items or 25% declared invalid. In the Anates package A program there are 30 questions or 75% declared valid and 10 questions or 25% declared invalid. In package B there are 27 questions or 67.5% declared valid and 13 items or 32.5% declared invalid; (2) Questions have high reliability; (3) The level of difficulty of easy questions; (4) Having good differentiation; (5) The function of the deception about the function; (6) An effective program for teachers to use is Iteman. While the benefit for the results or the value of students is Anates.